2020
DOI: 10.3390/biomedicines8110454
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Storage Protein Ferritin Is Upregulated in Endometriosis and Iron Overload Contributes to a Migratory Phenotype

Abstract: High levels of iron in the peritoneal cavity during menstruation have been implicated in the pathogenesis of endometriosis. However, whether iron directly affects the growth or migration of human endometriotic cells is poorly understood. This study demonstrated the presence of increased levels of the iron storage protein, ferritin, in the endometriotic tissues of patients with endometriosis. Furthermore, iron treatment stimulated the migration and epithelial–mesenchymal transition (EMT), but not growth, of 12Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…However, our retrospective analysis showed that oocyte quality was poorer in patients with OE than those with non-ovarian endometriosis (Table 1 ). Iron overload in the peritoneal fluid and FF of EMs patients is an important factor that leads to ectopic tissue proliferation and damage to oocytes [ 8 , 27 ], but the specific mechanism in which iron overload in the FF affects granulosa cells and oocytes has not been fully elucidated. Considering that follicles close to the OE lesion tissues exhibit higher total iron levels and lower oocyte retrieval rates than follicles in healthy ovaries [ 28 ], iron overload in the OE may impair oocyte maturation and function by affecting granulosa cells close to the lesion and further mediate the release of abnormal exosomes of granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, our retrospective analysis showed that oocyte quality was poorer in patients with OE than those with non-ovarian endometriosis (Table 1 ). Iron overload in the peritoneal fluid and FF of EMs patients is an important factor that leads to ectopic tissue proliferation and damage to oocytes [ 8 , 27 ], but the specific mechanism in which iron overload in the FF affects granulosa cells and oocytes has not been fully elucidated. Considering that follicles close to the OE lesion tissues exhibit higher total iron levels and lower oocyte retrieval rates than follicles in healthy ovaries [ 28 ], iron overload in the OE may impair oocyte maturation and function by affecting granulosa cells close to the lesion and further mediate the release of abnormal exosomes of granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Harvested tissue is suspended in 200 -500 µl of solution before injection into the peritoneal cavity. Solutions vary between studies, and include saline (Pittaluga et al, 2010;Uegaki et al, 2015;Ruiz et al, 2016;Dodds et al, 2017;Sanchez et al, 2017;Yan et al, 2019;Kim et al, 2020), Hank's Balanced Salt Solution (HBSS) (Fattori et al, 2020), phosphate-buffered saline (PBS) (Bacci et al, 2009;Chen et al, 2009;Altan et al, 2010;Jensen et al, 2010;Wieser et al, 2012;Tomio et al, 2013;Greaves et al, 2014;Heard et al, 2016;Yuan et al, 2018;Horne et al, 2019;Woo et al, 2020), and warmed Dulbecco's Modified Eagle Medium (DMEM) (Nowak et al, 2008). The solutions chosen mimic the salinity and pH of the peritoneal cavity and maintain viability of the uterine tissue.…”
Section: Intraperitoneal Injectionmentioning
confidence: 99%
“…It is possible that iron overload and iron-mediated free radical production cause the loss of TJs proteins and degeneration of endothelial cells, and that targeting iron mediated oxidative stress provides an extended therapeutic time window against an ischemic event ( Park et al, 2011 ; Won et al, 2011 ). Excess iron accumulation induced MMPs expression ( Woo et al, 2020 ). Studies have suggested that MMPs degrade the vascular basement membrane components, resulting in disruption of the BBB ( Jin et al, 2019 ), and that excess iron accumulation will initiate the Fenton reaction to generate ROS ( Xu et al, 2020 ).…”
Section: Ferroptosis In Blood-brain Barrier Degradationmentioning
confidence: 99%